Ethical climate of Public Sector organizations in Australia - Issa, Theodora; Pick, David (Society for Global Business & Economic Development (SGBED), 2011)
The aim of this paper is to identify and analyse the ethical climate in the Australian Public Sector organizations. Using a mixed method design, data was collected from 158 employees of all ranks using an online survey. Data analysis suggests that public servants rate highly such values as integrity, honesty, support and compassion that act as a positive force for making the workplace more tolerable, flexible, and most importantly, in support of an ethical climate that is accountable. However, some respondents expressed concerns that management do not necessarily maintain or display such values. This is reflected in the doubt cast by respondents that an individual with a self-serving (selfish) ethical mindset can be changed for the better. This suggests that there are a number of different possible ethical climates. Furthermore, the analysis suggests that respondents display a high level of respect for belief systems different to their own.While there are those who stated that they do not ‘wear their beliefs on their sleeves’, those belief systems come out in the way they treat others and the way they view the world. To improve the ethical climate of public service organizations, the data suggests that it is important to combat feelings amongst staff that favouritism is being practiced. Interestingly, respondents concede that this too is in the hands of management who they say ‘set the ethical scene’. Though limited to Australia, this research potentially adds to the developing business ethics literature generally and more specifically to the evolving theoretical perspectives on ethical mind-sets with the identification and development of ethical climate in organizations raising some interesting theoretical questions worthy of further research.